Estimating the burden of skin diseases using patient‐reported daily time trade‐off as a measure of disease impact and unmet needs - Yuki M. F. Andersen; Claus Zachariae; Simon Francis Thomsen; Jacob Pontoppidan Thyssen; Alexander Egeberg (Wiley, 2024)
Abstract Background Dermatological diseases may cause significantly impaired quality of life, however patient reported outcomes are often disease specific, and not comparable across diseases. Objectives To examine daily time trade‐off (dTTO), as a measure of disease burden. Methods An epidemiological study based on patient data from Danish Skin Cohort (prospective cohort of Danish dermatology patients) was conducted. Data were linked with routinely collected data from Statistics Denmark. We included adults with either alopecia areata (AA), atopic dermatitis (AD), hidradenitis suppurative (HS), psoriasis, or rosacea. All patients with a diagnostic code listed above were invited to participate. The primary outcome was defined as a dTTO of more than 30 minutes daily. Results A total of 680, 1605, 611, 1664, and 1698 adults with AA, AD, HS, psoriasis, and rosacea, respectively, were included. In multiple regression models, patients with AA were most likely to have a dTTO of more than 30 minutes, followed by patients with HS, AD, psoriasis and rosacea. A total of 33.7% (AA), 29.3% (HS), 14.6% (AD), 11.1% (psoriasis), and 9.0% (rosacea) of patients were willing to spend two hours or more per day. The dTTO correlated with disease severity and DLQI across disease groups. Conclusions Patients with AA, followed by HS were willing to spend most time on treatment, possibly reflecting unmet needs in these patient groups. Daily TTO correlated with perceived disease severity in all groups and may be a useful measure of dermatological disease burden.